Board gender diversity, financial performance, ESG and audit committee: Capturing ‘glass cliff’ phenomenon in emerging market - Nikmah, Alfa Lailatin; Hakim, Tito IM. Rahman; Kusno, Hendra Sanjaya (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study investigates the effect of board gender diversity on financial performance, using ESG performance and audit committee expertise as moderating variables. Utilizing a purposive sampling approach, a sample of 31 firms from the technology, healthcare, and energy sectors listed on the Indonesia Stock Exchange (IDX) between 2022 and 2023 was selected. The data were analyzed using panel data regression analysis. The results indicate that board gender diversity fails to significantly affect financial performance. Furthermore, ESG performance and audit committee expertise do not moderate the gender diversity and. financial performance dynamic. However, sensitivity tests employing alternative proxies for board gender diversity and financial performance reveal that the presence of female directors significantly affects accounting-based performance (ROE and ROA). Conversely, audit committee expertise positively moderates the impact of female directors on market-based performance (Tobin’s Q) across all board gender diversity proxies. Based on these findings, future research should employ the Blau and Shannon indexes to capture board gender diversity during post-crisis periods. Additionally, investors are advised to closely monitor firms with robust audit committee expertise, while policymakers are encouraged to formulate regulations that promote board consolidation with audit committees possessing advanced accounting and financial expertise during turbulent times.